Tislelizumab efficacy and safety compared to other anti–PD-1s: a network meta-analysis of first-line therapies for unresectable, locally advanced or metastatic esophageal squamous cell carcinoma - Ajani, Jaffer A.; Smyth, Elizabeth; Tougeron, David; Jung, Hyun Ae; Tang, Wenxi; Steenkamp, Jason; Prentiss, Emily; Coaquira Castro, JeanPierre; Szafranski, Kirk; Zhan, Lin (Frontiers in Immunology, 2026)
IntroductionThe addition of programmed cell death protein-1 (PD-1) inhibitors to chemotherapy (CT) or anti-CTLA4 (ipilimumab) has recently emerged as an effective first-line (1L) treatment for esophageal squamous cell carcinoma (ESCC), the most common form of esophageal cancer globally.MethodsA systematic literature review (SLR) was conducted to identify randomized controlled trials (RCTs) investigating 1L PD-1 inhibitor regimens in adult patients with unresectable, locally advanced, or metastatic ESCC. Bayesian NMAs were conducted to evaluate overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and grade ≥3 treatment-related adverse events (TRAEs).ResultsThree eligible RCTs were identified, evaluating three PD-1 inhibitor regimens with broad regulatory approval for 1L ESCC in combination with CT (tislelizumab, nivolumab, and pembrolizumab). Tislelizumab + CT demonstrated similar long-term OS to nivolumab + CT and pembrolizumab + CT but a significant PFS benefit over nivolumab + CT and comparable efficacy to pembrolizumab + CT. Subgroup analyses were consistent with the base case, including among patients with varying PD-L1 expression (≥1% and ≥5% Tumor Area Positivity [TAP] score or ≥1 and ≥5 combined positive score [CPS]), Asia versus the rest of world, and different underlying CT backbones. Safety profiles were comparable across the three treatments.ConclusionTislelizumab + CT is an effective 1L treatment option for advanced or metastatic ESCC, demonstrating comparable efficacy and safety outcomes relative to existing treatments.